Global exponential stability of a class of impulsive cellular neural networks with supremums. (18th October 2013) - Stamova, Ivanka; Stamov, Trayan; Li, Xiaodi
SUMMARY In this paper, we study the problem of global exponential stability for impulsive cellular neural networks with time‐varying delays and supremums. Using Young's inequality and Lyapunov‐like functions, new stability criteria are proved. Because supremums and impulses are relevant in various contexts, including problems in the theory of automatic control, our results can be applied in the qualitative investigations of many practical problems of diverse interest. Copyright © 2013 John Wiley & Sons, Ltd.